Educação permanente em saúde como um espaço intersseçor de uma residência multiprofissional: estudo de caso - Silva, Cristiane Trivisiol da (2013)
The research had as general objective describe how the permanent education in health is developed by professionals in the multi-professional residence and as specific objectives: identify the perception of professional members of RMIS on EPS; learn how the EPS is developed in the everyday life of these professionals and understand how the EPS permeates the formation of residents. Was characterized by a qualitative approach of type case study which was carried out in a teaching hospital, a city in the interior of Rio Grande do Sul with seventeen members of Residence Multidisciplinary professionals incorporated into the public health system. The data were collected in the period from January to may 2012 through documentary analysis, systematic observation and semi-structured interview. Been complied with all ethical aspects of research with humans based on Resolution 196/96 of the National Health Council. The organization and the processing of data was carried out using the Atlas Software You 6.2. Data analysis occurred by means of thematic content analysis will Minayo that showed three categories: Professional members of RMS ' perception about the permanent education in health; RMIS as intercessor for the development of EPS and EPS as device of training professionals in health in RMIS. The results pointed to the understanding of the members of the multidisciplinary residency regarding permanent education in health beyond a strategic action. Also, evidence for the identification of multidisciplinary residency as a intersseçor space that permeates the formation of resident based on the concepts of permanent education in health which allows reflection of their practice articulating the attention and management spheres, as well as seeking the integration between theory and practice and multidisciplinary action as producers of health actions. It is concluded that there is a need for further research with greater depth and under other spaces of manifestation of EPS.